Ethical Codes of Conduct in Teaching Practice: : The Case of South African Universities - Kriel, Carike; Livingston, Candice; Kwenda, Chiwimbiso (International Journal of African Higher Education, 2022)
The lack of codes of ethics and codes of conduct in teaching practice is of international concern, with South African universities seemingly lagging behind in recent research. This study aimed to establish the status of ethical codes and procedures regarding teaching practice at South African universities, and what is included in such codes. Critical content analysis was conducted of the ethical policies posted on the universities’ websites. The analysis revealed that most South African universities have not enacted dedicated ethical codes of conduct for teaching practice. It was also found that the elements included in the codes vary across universities. Due to the unique nature of ethical dilemmas relating to teaching practice, this is cause for grave concern. A lack of ethical codes poses potential risks for various role players in teaching practice. The concerns include but are not limited to, unethical relationships between pre-service teachers and staff members, unfair treatment of learners, and teaching incorrect information due to a lack of competence. Key words: pre-service teachers, teaching practice, code of conduct, code of ethics